Does the Code of Conduct Moderate Corporate Attributes and Carbon Emissions Disclosure? - Andrian, Tommy; Sudibyo, Yvonne Augustine (Journal of Accounting, Business and Finance Research, 2021)
The objective of this study is to analyze the effects of corporate attributes proxied by green strategy, institutional shareholding, and board of directors, with the code of conduct as a moderating variable on carbon emissions disclosure. Previous research has used many variables that affect carbon emissions disclosure, but there are a few studies that use a corporate code of conduct to strengthen the relationship between each variable and disclosure of carbon emissions. This study uses the measurement of the corporate code of conduct, which is based on the highest index results for disclosing carbon emissions. A quantitative approach was used with 140 observations from 28 consumer goods companies listed on the Indonesia Stock Exchange (IDX) from 2015–2019. The data were analyzed using a moderating regression analysis. The results found that green strategies have a positive and significant influence on carbon emissions disclosure, while institutional shareholding and board of directors have no influence on carbon emissions disclosure. Therefore, the code of conduct can strengthen the relationship between green strategies and carbon emissions disclosure. However, the code of conduct cannot moderate the relationship between institutional ownership and the board of directors on carbon emissions disclosure. Companies must take advantage of opportunities from the impact of climate change through a green strategy through the implementation of an effective corporate code of conduct to strengthen their competitive advantage through disclosure of carbon emissions information.